Career Services in University External Relations. Issue 148 (December 2014) - Hayden, Seth C. W.; Ledwith, Katherine E.
Abstract : The chapter will focus on the role of career services in external relations. It will provide the basis for this connection along with best practices in developing and maintaining a mutually beneficial relationship between career centers and on‐campus and off‐campus partners.